2017
DOI: 10.21037/jtd.2017.04.67
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative care for aortic surgery using circulatory arrest

Abstract: Abstract:The total circulatory arrest (CA) is necessary to achieve optimal surgical conditions in certain aortic pathologies, especially in those affecting the ascending aorta and aortic arch. During this procedure it is necessary to protect all the organs of ischemia, especially those of the central nervous system and for this purpose several strategies have been developed. The first and most important protective method is systemic hypothermia. The degree of hypothermia and the route of application have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…5,12,14,15,36,39 Catapano et al 39 analyzed that there is a positive association between high values of mean arterial pressure and neurological improvement in patients with spinal cord injury. Ullery et al 40 came to the same conclusion in patients who had undergone a correction of aortic aneurysm; they also added that the mean arterial pressure < 70 mm Hg is a risk factor for spinal cord ischemia. The goal is to keep the mean arterial pressure at least 80 mm Hg for a surgical procedure that produces spinal ischemia, such as an aorta-related procedure, and maintain this goal by suspending 24 to 72 hours, adding any hypertensive agent if necessary.…”
Section: Maintenance Of Mean Arterial Pressurementioning
confidence: 80%
See 1 more Smart Citation
“…5,12,14,15,36,39 Catapano et al 39 analyzed that there is a positive association between high values of mean arterial pressure and neurological improvement in patients with spinal cord injury. Ullery et al 40 came to the same conclusion in patients who had undergone a correction of aortic aneurysm; they also added that the mean arterial pressure < 70 mm Hg is a risk factor for spinal cord ischemia. The goal is to keep the mean arterial pressure at least 80 mm Hg for a surgical procedure that produces spinal ischemia, such as an aorta-related procedure, and maintain this goal by suspending 24 to 72 hours, adding any hypertensive agent if necessary.…”
Section: Maintenance Of Mean Arterial Pressurementioning
confidence: 80%
“…It should be noted that oxygen participates in the reactions of cell respiration and cell death, so that interruption of use is key to prevent the neuronal damage after the blood supply is suspended. 40 Hypothermia is neuroprotective as it seeks to reduce the rate of oxygen metabolism. 40 Hypothermia reduces intracellular enzyme activity by 6 to 7% per degree of temperature reduction; also, it reduces glutamate release or enhanced release of GABA, suppresses intracellular calcium intake, and decreases free radical generation to result in mitigation of harmful response of reperfusion.…”
Section: Hypothermiamentioning
confidence: 99%
“…An analysis of the German Registry for Acute Aortic Dissection Type A revealed that 50% of patients undergoing surgery for ATAAD received at least one neuroprotective drug, indicating a slight advantage for the use of steroids in terms of neurological outcomes [ 79 ]. However, further scientific evidence supporting the implementation of neuroprotective pharmacological treatment is low, while no significant benefit has been shown in larger clinical trials yet [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the hypothermic circulatory arrest, known to increase the risk of complications. 21,22 After elective aortic hemiarch reconstruction, a combined GI bleeding and ischemia rate of 3.3% to 3.9% was shown. 23 Likewise, the longer duration of surgery and longer time on ECC in the AGI ≥2 group can be attributed to the difference in types of surgery.…”
Section: Discussionmentioning
confidence: 97%